Migration Policy, African Population Growth and Global Inequality - Andrew Mountford; Hillel Rapoport (Institute for the Study of Labor (IZA), 2014)
According to recent UN projections more than 50 percent of the growth in world population over the next half century will be due to population growth in Africa. Given this, any policy that influences African demography will have a significant impact on the world distribution of income. In this paper we discuss the potential for migration policies to affect fertility and education decisions, and hence, population growth in Africa. We present the results from different scenarios for more or less restrictive/selective migration policies and derive their implications for the evolution of world inequality.
Keywords: O40; F11; F43; 330; global inequality; migration; fertility; Africa